2020
DOI: 10.1177/0263617420922014
|View full text |Cite
|
Sign up to set email alerts
|

Novel reusable functionalized magnetic cobalt ferrite nanoparticles as oil adsorbents

Abstract: Magnetic nanoparticles are amongst the most promising adsorption materials for oil spill clean-up due to their high surface area, ease of functionalization with high oil affinity and facile separation after the cleaning process with an external magnetic field. In this work, we successfully synthesized magnetic cobalt ferrite nanoparticles (CoFe2O4 NPs) that were electrostatically stabilized and functionalized with various alkoxysilanes for effective oil adsorption and oil spill removal. Additionally, the adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The vibration from the stretching of the Si–O–Si group can be identified in the bands of 1056 and 1093 cm −1 . The presence of these bands in the FTIR spectrum ( Figure 1 (a)), confirms that the silica samples in the sol-gel system were obtained satisfactorily [ 51 , 52 , 53 , 55 ].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The vibration from the stretching of the Si–O–Si group can be identified in the bands of 1056 and 1093 cm −1 . The presence of these bands in the FTIR spectrum ( Figure 1 (a)), confirms that the silica samples in the sol-gel system were obtained satisfactorily [ 51 , 52 , 53 , 55 ].…”
Section: Resultssupporting
confidence: 61%
“…In the spectrum of the composite without chitosan (0%Chi), the characteristic signs Si–OH of the silica (TEOS) can be observed in the bands of 2361 and 969 cm −1 respectively, which are stretching of the silanol groups present in the silica [ 51 , 52 , 53 , 54 ]. The vibration from the stretching of the Si–O–Si group can be identified in the bands of 1056 and 1093 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“… 25 The favorable properties of silica gel such as environmental friendliness, high chemical stability, low cost, variety of possible structures, range of functionalization methods and control of reactions due to lower reactivity have led to its widespread use in the industry. 26,27 Similarly, Mandizade et al evaluated the adsorption of sulfur from model fuel using AFe 2 O 4 (A: Ni, Cu, Zn)–activated carbon nanocomposite and found that NiFe 2 O 4 –activated carbon with BET surface area 626 m 2 g −1 is the best adsorbent for producing clean fuel. 28 Maximum adsorption capacity ( q m ) of the NiFe 2 O 4 –AC nanocomposite was 108 mg g −1 for sulfur compound.…”
Section: Introductionmentioning
confidence: 99%
“…For glutaraldehyde and amine linking to SiNPs to produce f-SiNPs, polydopamine formation on COVRs, and NHS-PEG 4 -biotin enrichment to enhance ST-polyHRP affinity, and S-protein rebinding to COVRs (Figure S2 and Table S1). Common bands in all spectra around 1150–1020 cm –1 are due to Si–O–Si longitudinal (1140 cm –1 ) and transverse (1020 cm –1 ) and Si–O–C (1108 cm –1 ) stretching modes of the siloxane framework. Peaks appearing at 1600–1900 and 3378 cm –1 are consistent with amide bond formation between (3-aminopropyl) triethyloxysilane (APTES) and glutaraldehyde that anchors the S-protein on the surface . The 1644 cm –1 band found after glutaraldehyde cross-linking to SiNPs reveals how APTES connects in 3D space via imine bond formation .…”
Section: Resultsmentioning
confidence: 82%